Breathing, postural stability, and psychological health: a study to explore triangular links - Tassani, Simone; Chaves, Paula; Beardsley, Marc; Vujovic, Milica; Ramírez, Juan; Mendoza, Jimena; Portero-Tresserra, Marta; González-Ballester, Miguel Angel; Hernández-Leo, Davinia (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: This study aims to test the hypothesis that breathing can be directly linked to postural stability and psychological health. A protocol enabling the simultaneous analysis of breathing, posture, and emotional levels in university students is presented. This aims to verify the possibility of defining a triangular link and to test the adequacy of various measurement techniques. Participants and Procedure: Twenty-three subjects (9 females and 14 males), aged between 18 and 23 years, were recruited. The experiment consisted of four conditions, each lasting three minutes: Standard quiet standing with open eyes (1), with closed eyes (2), and relaxed quiet standing while attempting deep abdominal breathing with open eyes (3) and with closed eyes (4). These latter two acquisitions were performed after subjects were instructed to maintain a relaxed state. Main Outcome Measures: All subjects underwent postural and stability analysis in a motion capture laboratory. The presented protocol enabled the extraction of 4 sets of variables: Stabilometric data, based on the displacement of the center of pressure and acceleration, derived respectively from force plate and wearable sensors. Postural variables: angles of each joint of the body were measured using a stereophotogrammetric system, implementing the Helen Hayes protocol. Breathing compartment: optoelectronic plethysmography allowed the measurement of the percentage of use of each chest compartment. Emotional state was evaluated using both psychometric data and physiological signals. A multivariate analysis was proposed. Results: A holistic protocol was presented and tested. Emotional levels were found to be related to posture and the varied use of breathing compartments. Abdominal breathing proved to be a challenging task for most subjects, especially females, who were unable to control their breathing patterns. In males, the abdominal breathing pattern was associated with increased stability and reduced anxiety. Conclusions: In conclusion, difficulties in performing deep abdominal breathing were associated with elevated anxiety scores and decreased stability. This depicts a circular self-sustaining relationship that may reduce the quality of life, undermine learning, and contribute to muscular co-contraction and the development of musculoskeletal disorders. The presented protocol can be utilized to quantitatively and holistically assess the healthy and/or pathological condition of subjects.